Cholesterol crystals in non-culprit plaques of STEMI patients: A 3-vessel OCT study. (1st October 2022) - Qin, Zhifeng; Cao, Muhua; Xi, Xiangwen; Zhang, Yanwen; Wang, Zhuozhong; Zhao, Suhong; Tian, Yanan; Xu, Qinglu; Yu, Huai; Tian, Jinwei; Yu, Bo
Abstract: Background: Cholesterol crystals (CCs) are regular microstructures found within the necrotic core of atherosclerotic plaques and have been hypothesized to be related to plaque destabilization. We attempted to investigate the potential association between CCs and non-culprit plaque vulnerability in patients with ST-segment elevated myocardial infarction (STEMI) and study morphological features of CCs in ruptured non-culprit plaques. Methods: A total of 261 patients with ST-segment elevation myocardial infarction who underwent 3-vessel optical coherence tomography (OCT) imaging were included. Non-culprit plaques were divided into two groups according to the presence or absence of CCs in the plaque to compare the morphological characteristics of the plaques. The differences in parameters of the non-culprit plaque CCs were explored between ruptured plaques and unruptured plaques. Results: Totally, 530 non-culprit plaques (29 ruptured plaques and 501 unruptured plaques) were identified by OCT. The incidence of CCs was 21.1%. Compared with non-culprit plaques without CCs, those with CCs had a larger lipid burden. Macrophages ( p  < 0.001) and spotty calcification ( p  = 0.002) were more frequently observed in non-culprit plaques with CCs. The frequency of CCs was significantly higher ( p  = 0.001) and the CCs were larger ( p  = 0.046) and more superficial ( p  = 0.005) in ruptured non-culprit plaques than in unruptured non-culprit plaques. The maximum lipid arc and fibrous cap thickness were independent predictors of plaque rupture, but the presence of CCs was not. Conclusions: Non-culprit plaques with CCs have more vulnerable features. CCs are more frequently found in ruptured non-culprit plaques and larger and more superficial CCs are associated with plaque rupture. Highlights: This 3-vessel OCT study involved a comprehensive assessment of the incidence and morphology of non-culprit CCs. CCs may be associated with non-culprit plaque instability. Large and superficial CCs have been found in plaques with previous rupture.